An Analysis of Bitcoin Acceptance in Indonesia - Gunawan, Fergyanto E.; Novendra, Rizki (Bina Nusantara University, 2017)
This research intended to understand the factors affecting the acceptance of Bitcoin technology in Indonesia. It adopted the model of Unified Theory of Acceptance and Use of Technology (UTAUT), which took into account four influencing factors. Those were performance expectancy, effort expectancy, social influence, and facilitating conditions. The factors of gender and age were assumed to moderate the relations between those four factors and use and behavioral intention. The empirical data for those factors were collected by questionnaires from 49 respondents. The statistical significance of the relationships was evaluated by multivariate regression analysis. The result is a model that matches the data with R2 = 0,678. It demonstrates a high level of fitness. The analysis suggests that the performance expectancy factor and the social influence factor greatly affect the behavioral intention to use Bitcoin with the values of t-statistic of 3,835 (p-value = 0,000) for the former factor and 1,948 (0,059) for the latter factor. However, the social influence factor has less profound effect on the behavioral intention.